"La visita del embajador de mexico sr. Tejeda a la colectividad de los campesinos de Barcelona, zona de Pla de Marti". Left Tejeda with his daughter. Right next to him Aguilar. Copied from CNT collection. Series of 8 photos
"La visita del embajador de mexico sr. Tejeda a la colectividad de los campesinos de Barcelona, zona de Pla de Marti". Left Tejeda with his daughter. Right next to him Aguilar. Copied from CNT collection. Series of 8 photos.